Economic Integration, Currency Areas, and Macroeconomic Policy - Douglas D. Purvis (Queen's University, Department of Economics, 1992)
In this essay I explore the implications of regional economic integration for the currency arrangements appropriate within and between regions. This topic is motivated by the recent rekindling of interest in fixed exchange rates which, in turn, has been due in part to disappointment in the performance of the flexible exchange rate system that has evolved over the past two decades, and in part to the increased regional economic integration that the world economy has witnessed in the past decade. i review some of the issues pertaining to the performance of flexible exchange rates, but the primary focus of the essay is on the exchange rate implications of economic integration. The essay returns to many of the issues raised in Robert Mundell's classic 1961 essay, "A Theory of Optimal Currency Areas". that essay was written in large part as a cautionary reaction to the apparent increasing favor that flexible exchange rates were gaining with economists at the time. Much of the focus of the recent literature is on the case for fixed exchange rates arising out of the creation of a "single-market" under the Europe 1992 program for European monetary union. In contrast, in this paper I focus on issues arising from the current Canadian situation. Of particular interest is the Canada-US Free Trade Agreement signed in January 1988, and which now appears likely to evolve into a broader North American Free Trade Agreement, or NAFTA, incorporating Mexico. While the FTA to date has not given rise to any strong constituency for a North American monetary union, the increased international integration that the FTA and NAFTA represent, combined with recent and prospective developments related to our constitutional negotiations which might be viewed as weakening aspects of the Canadian economic union, have led to renewed interest in the debate over whether Canada's national interests might be better served with a fixed exchange rate vis a vis the US dollar. I reject the case for a fixed Canada-US exchange rate, and argue that the current Bank of Canada regime–a flexible exchange rate with a medium-term inflation target–is not only appropriate but the only one supported by available evidence and theory about how the economy functions. But choosing the right regime is not a panacea; good results still require good policy.
Keywords: O23; 423; 432; 330; currency area; economic integration; exchange rate regimes